To die or not to die? Lessons from lesion mimic mutants - Bruggeman, Quentin; Raynaud, Cécile; Benhamed, Moussa; Delarue, Marianne (Frontiers in Plant Science, 2015)
Programmed cell death (PCD) is a ubiquitous genetically regulated process consisting in an activation of finely controlled signaling pathways that lead to cellular suicide. Although some aspects of PCD control appear evolutionary conserved between plants, animals and fungi, the extent of conservation remains controversial. Over the last decades, identification and characterization of several lesion mimic mutants (LMM) has been a powerful tool in the quest to unravel PCD pathways in plants. Thanks to progress in molecular genetics, mutations causing the phenotype of a large number of LMM and their related suppressors were mapped, and the identification of the mutated genes shed light on major pathways in the onset of plant PCD such as (i) the involvements of chloroplasts and light energy, (ii) the roles of sphingolipids and fatty acids, (iii) a signal perception at the plasma membrane that requires efficient membrane trafficking, (iv) secondary messengers such as ion fluxes and ROS and (v) the control of gene expression as the last integrator of the signaling pathways.